Spinal pain: causes and treatment policy - Yu. A. Olyunin (Современная ревматология, 2018)
Chronic pain in the spine is one of the most urgent medical problems. Clinical and instrumental studies fail to reveal that most patients with back pain have any structural changes that may contribute to its occurrence. It is considered that the pain may be caused by the strain of muscles and ligaments located in the lower back, by the overload of these segments, and by detraining. If the cause of the pain syndrome cannot be established, the pain in the spine is regarded as nonspecific. It is believed that behavioral, psychological, and social factors can play an important role in the development of pain. Therefore, current guidelines propose to apply a biopsychosocial approach in patients with back pain. At the same time, much attention is paid to patient self-treatment, exercise therapy, psychotherapy, and some other auxiliary methods. When nonpharmacological interventions are insufficiently effective, drug therapy is indicated. Nonsteroidal anti-inflammatory drugs (NSAIDs), paracetamol, opioid analgesics, and muscle relaxants are used to treat nonspecific spinal pain. Pharmacotherapy is usually initiated with the use of NSAIDs. They can effectively relieve pain sndrome, but the possibilities of their use in a large proportion of patients are significantly limited due to adverse reactions (ARs). Gastrointestinal and cardiovascular ARs most commonly occur. The likelihood of ARs can be substantially reduced by the use of aceclofenac (AirtalR) that is characterized by a favorable gastrointestinal and cardiovascular safety profile. Paracetamol, opioid analgesics, and muscle relaxants are also used in the combination treatment of these patients.